2019
DOI: 10.1002/stc.2439
|View full text |Cite
|
Sign up to set email alerts
|

Vibration‐based damage localization with load vectors under temperature changes

Abstract: Damage detection and localization in civil or mechanical structures is a subject of active development and research. A few vibration-based methods have been developed so far, requiring, for example, modal parameter estimates in the reference and damaged states of the investigated structure, and for localization

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…These tasks can be addressed based on damage‐sensitive features that are defined in the reference (healthy) state of the system and that are evaluated for damage diagnosis during the operating states of the structure. Since the considered features are computed from vibration measurements, they may be affected by noise and changing environmental conditions, like variable temperature or excitation 2–4 . When not accounted for, those changes may lead to false alarms, a characteristic that impedes their application for structural monitoring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These tasks can be addressed based on damage‐sensitive features that are defined in the reference (healthy) state of the system and that are evaluated for damage diagnosis during the operating states of the structure. Since the considered features are computed from vibration measurements, they may be affected by noise and changing environmental conditions, like variable temperature or excitation 2–4 . When not accounted for, those changes may lead to false alarms, a characteristic that impedes their application for structural monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Reviews of the early developments of vibration‐based damage detection can be found in previous studies 29–31 . The performance of these methods is conditioned on several factors, for example, the quality of parameters estimated from the data, the availability of large amount of training data from different damage scenarios, 26 the ability to track the selected parameter estimates after identifying them from the healthy state of the structure, 32 and the ability to account for changing environmental conditions like the temperature, 4 amongst other factors.…”
Section: Introductionmentioning
confidence: 99%
“…These variabilities, which are governed by the temperature, wind speed, humidity, excitation level, and so forth, are known to camouflage damaged-induced changes in the feature set and thus deteriorate the damage detectability [3]. Several studies have noted that the temperature constitutes the most influential parameter [4,5,6,7,8,9], and therefore we limit this paper to investigate the effect of temperature-induced variability.…”
Section: Introductionmentioning
confidence: 99%
“…Structural physical parameters will be altered due to structural damage, which will result in a difference in the corresponding dynamic characteristics (e.g., natural frequency, mode curvature, and strain mode), through which structural damage can be identified [6][7][8][9]. Several studies have focused on damage identification based on structural global responses.…”
Section: Introductionmentioning
confidence: 99%